Method of Instinbāth Law of Money Waqf Abu Hanifah Immediate Perspective - Mustafa Kamal; Hanafiyah Hanafiyah; Nainunis Nainunis; Safrizal Safrizal; Munawir Munawir; Saipul Bahri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This research should be done to find out how to explore and understand the contents of the text (Instinbāth pattern) of waqf legal money from the perspective of Imam Abi Hanifah. This research rests on the Instinbāth theory of Islamic law in establishing laws for the next generation. The library research uses descriptive analytical methods. The approach used in this study is referring to usul fiqh and Maqāshid al-Syāri'ah. These two approaches are used to analyze how the pattern of Instinbāth of law, as well as the constructs of the fiqh thought of Imam Abi Hanifah. From this study it can be concluded that: the pattern of istinbāth of Imam Abu Hanifah, first, in terms of coverage of nāsh from the three sources of waqf law (Q.S al-Māidah: 103, the narrative of Ibn Masūd, and the hadith of ibn 'Abbās)) dhahir lafadh al-nāsh shows the lack of encouragement of muamalah by carrying out the action of "al-Habsu" (waqf), because he can match the habits of Arab Jahiliyah who are used to the practice of Bahira, Sāibah, Washīlah, and Hām as explained in the Qur'an. Both istinbāth al-Ma'āny, through the approach: Isyārah al-Nāsh, dilālah al-Nāsh, and Iqtidhā 'al-Nāsh (analysis of the relevance of the meaning) according to Imam Abu Hanifah it can be understood that mu'amalah waqf does not contain' luzūm contract '( where an object that has been represented remains in the possessor's ownership with his tasharruf rights). On the basis of this istinbāth according to Imam Abu Hanifah cash may be represented, because in principle the mawqūf (waqf object) remains in the power of belonging to the apostle.